Regional composition of national house price cycles in the US - Jan Prüser; Torsten Schmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
House price cycles may have considerable macroeconomic effects even if they evolve heterogeneous across local markets. In this paper we use a panel Markov switching model allowing for time-varying volatility to analyze national and state level house price regimes for the US jointly. Our approach identifies three house price regimes endogenously. A nationwide boom regime, a spatially limited bust regime and a nationwide bust regime. The spatially limited bust regime occurs in the coastal states where compared to other states the population density is high, the unemployment rate, the housing density as well as the land supply elasticity is low. This spatially limited bust regime usually follows a nationwide house price boom. Hence, house price movements in the coastal states usually determine the nationwide cycle in the US. Moreover, boom and bust cycles are accompanied by an exaggeration of house price increases during the boom in this group of states. In contrast, a bubble in the housing market occored in almost all states previous to the Great Recession. This is one explanation for the severity of the Great Recession. – – Hauspreiszyklen können erhebliche makroökonomische Auswirkungen haben, auch wenn sie sich in einzelnen Regionen unterschiedlich entwickeln. In diesem Beitrag verwenden wir ein Panel-Markov-Switching-Modell, das zeitvariable Volatilität berücksichtigt, um die nationalen und bundesstaatlichen Hauspreisregime für die USA gemeinsam zu analysieren. Unser Ansatz identifiziert drei Hauspreisregime. Ein natinales Boomregime, ein räumlich begrenztes Bustregime und ein nationales Bustregime. Das räumlich begrenzte Bustregime tritt in den Küstenstaaten auf, wo im Vergleich zu anderen Staaten die Bevölkerungsdichte hoch, die Arbeitslosenquote, die Wohnungsdichte sowie die Elastizität des Landangebots gering ist. Dieses räumlich begrenzte Bustregime folgt in der Regel einem landesweiten Hauspreisboom. Daher gibt es einen Gleichlauf der Hauspreisbewegungen in den Küstenstaaten und dem nationalen Zyklus in den USA. Darüber hinaus gehen Boom- und Bustzyklen in dieser Staatengruppe mit einer Übertreibung der Hauspreissteigerungen während des Booms einher. Im Gegensatz dazu kam es in fast allen Bundesstaaten vor der Großen Rezession zu einer Blase auf dem Immobilienmarkt. Dies ist eine Erklärung für die Schwere der Großen Rezession.
Keywords: E31; R31; C11; C32; 330; house price cycles; regional house prices; Markov switching